Twelve tips to revitalise problem-based learning. (3rd August 2015) - Wood, Sarah J.; Woywodt, Alexander; Pugh, Mark; Sampson, Ian; Madhavi, Paladugu
Abstract: The role of the problem-based learning (PBL) facilitator has seen different interpretations ever since PBL first gained widespread use. What has remained unchanged is the challenge for facilitators to use their knowledge and expertise sparingly and to use their interpersonal skills to improve group dynamics. Medical undergraduates attending PBL sessions have also changed in their skill sets, expectations and the use of technology. Based on the published literature and a recent faculty workshop, we provide PBL facilitators and institutions with 12 tips on how to make PBL more vibrant and interesting. We discuss our tips with reference to published literature and International Academy of Medical Education (AMEE) guidance. Our tips help students to engage with PBL, avoid monotony and make this teaching format more vibrant and fun for all involved. Introducing greater variety to the PBL process may also help with group dynamics by catering for a broader audience with different learning styles.